Conceptual framework for service quality and adjustments towards international students' satisfaction in Malaysia universities - Hamzah, Nurul Hamiza; Abdullah, Sahadah (2018)
Internationalization is a complex phenomenon in the field of higher education. Besides that, it is one of the important transformation processes of developing countries towards globalization. Generally, Malaysia is fast becoming one of the main education attractions among the international students from other countries around the world. International student enrolments make a vital economic contribution to universities in the whole region of the world.Delivering the high level of service quality is critically important in order to generate and maintaining loyal customers.Thus, exceptional levels of service quality lead to satisfy customers that may recommend the product or service among their friends.Student satisfaction has been one of the ‘core’ factors in retaining and attracting international students in the context of educational institutions. Satisfied students will help to attract more potential future customers (new students) to the institutions/universities through positive word of mouth (WOM) communication, increased students’ loyalty and the good image of the higher education institution.However, to satisfy the customers from different background and different culture will be even more difficult.Adjusting to a new culture can be so challenging and stressful experience for international students. Racial discrimination, language problems, accommodation difficulties, dietary restrictions, financial problems, and loneliness are the common and unique problems that they faced when they were in the host countries. Therefore, this paper proposes a model that links service quality, adjustments and international students’ satisfaction in Malaysian universities. Implication for future research, discussion and overall conclusion are also presented at the end of the paper.